Diversity of Dragonfly Species (Odonata) in the Tun Telanai Lake Ecosystem at Jambi University, Indonesia - Ananda, Evrillia Firmawati; Pasaribu, Hermina; Fadzillah, Naily; Azzahra, Ismi Dewi; Rivana, Maya; Pane, Sabrina; Rhamadani, Amanda; Adriadi, Ade; Wulandari, Tia (RUMPHIUS, 2026)
Lakes are among the most complex aquatic ecosystems, as they support a wide variety of organisms. One of the organisms commonly found in lake ecosystems is the dragonfly (Order Odonata). Ecologically, dragonflies play important roles, including acting as predators in the food chain that help regulate insect populations and serving as bioindicators of water quality. The presence and diversity of dragonflies are closely related to environmental conditions, particularly water quality and surrounding vegetation. This study aims to examine the species diversity of dragonflies in the Tun Telanai Lake area at Jambi University. A descriptive quantitative method was employed, involving direct observation and identification of dragonfly species found in the study area. The results of the identification revealed the presence of three dragonfly families comprising a total of ten species. The family Libellulidae was the most dominant, represented by seven species, followed by the family Gomphidae with two species, and the family Coenagrionidae with one species. The calculation of the Shannon–Wiener diversity index (H’) yielded a value of 1.29, which falls within the moderate diversity category. This result indicates that the habitat conditions and aquatic ecosystem of Tun Telanai Lake are relatively stable and capable of supporting dragonfly populations.